Management and Utilization of Clean Water at Bacan Coastal Fisheries Port, South Halmahera Regency - Darmawaty, Darmawaty; Mesrawaty, Mesrawaty (Agrikan Jurnal Agribisnis Perikanan, 2023)
Bacan Coastal Fisheries Port is one of the ports constructed to support the success of capture fisheries in the waters of South Halmahera. One of the functional facilities provided to support this endeavour is the provision of clean water. Adequate clean water must be available in sufficient quantity to facilitate activities at Bacan Coastal Fisheries Port. Therefore, this research aims determine the level of need and actual utilization of clean water at Bacan Coastal Fisheries Port. This research was conducted from April to September 2023 using a case study method and quantitative descriptive analysis. The research results indicate that the clean water used at Bacan Coastal Fisheries Port is sourced from surface wells with a total capacity of 30 cubic meters. The level of clean water needs at Bacan Coastal Fisheries Port is 18.7%, while the actual utilisation of clean water is 87.5%, and the theoretical utilisation rate is 4.67%.